2020
DOI: 10.18632/aging.103135
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SYK inhibitor, R406 as a novel senolytic agent

Abstract: The selective removal of senescent cells by senolytics is suggested as a potential approach to reverse aging and extend lifespan. Using high-throughput screening with replicative senescence of human diploid fibroblasts (HDFs), we identified a novel senolytic drug R406 that showed selective toxicity in senescent cells. Using flow cytometry and caspase expression analysis, we confirmed that R406 caused apoptotic cell death along with morphological changes in senescent cells. Interestingly, R406 altered the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…However, the compound showed low potency, which could be a result of Syk's upstream position in the signalling pathway, such that low level activity may be amplified through the signal cascade. We show that BAY 61-3606 significantly inhibited p38MAPK α/β activity as evidenced by the reduction in HSP27 phosphorylation, which concurs with the work by Alhazmi et al and suggesting that Syk kinase is upstream of p38MAP kinase, and several other reports showing Syk inhibition led to inhibition of phosphorylation of p38MAPK [80][81][82]. However, given inhibition was not complete there are likely to be other pathways controlling p38MAPK activation.…”
Section: Plos Onesupporting
confidence: 92%
“…However, the compound showed low potency, which could be a result of Syk's upstream position in the signalling pathway, such that low level activity may be amplified through the signal cascade. We show that BAY 61-3606 significantly inhibited p38MAPK α/β activity as evidenced by the reduction in HSP27 phosphorylation, which concurs with the work by Alhazmi et al and suggesting that Syk kinase is upstream of p38MAP kinase, and several other reports showing Syk inhibition led to inhibition of phosphorylation of p38MAPK [80][81][82]. However, given inhibition was not complete there are likely to be other pathways controlling p38MAPK activation.…”
Section: Plos Onesupporting
confidence: 92%
“…However, the transcriptional heterogeneity ( Hernandez-Segura et al, 2017 ) and the diverse tissue origins of SnCs, render SnCs depend on different SCAPs to maintain their survival, which makes it a challenge to develop certain senolytics to eliminate SnCs in various cell types. For example, we found that ABT263 is very potent to selectively kill senescent human lung diploid fibroblasts (HDF) ( Chang et al, 2016 ; He et al, 2020b ), but it does not work in senescent HDF isolated from human foreskins ( Cho et al, 2020 ), suggesting that HDF from different tissue origins may have different apoptotic resistance mechanisms. Therefore, gaining deep insights into the apoptosis-resistant proteins or pathways of SnCs may help to develop cell-specific or broad-spectrum senolytics to clear SnCs.…”
Section: Targeting Senescent Cells With Senolytics and New Strategiesmentioning
confidence: 99%
“…Later, they reported that the focal adhesion kinase (FAK) might differently regulate apoptosis and focal adhesion formation in SnCs ( Ryu et al, 2006 ). Furthermore, they identified a novel senolytic drug R406 that showed selective toxicity in HDF by inhibiting FAK and p38MAPK activity ( Cho et al, 2020 ). They also found that the major vault protein (MVP) was markedly increased in senescent HDF as well as in aged organs, downregulation of MVP increased the sensitivity of senescent HDF to apoptosis by modulation of Bcl-2 expression ( Ryu et al, 2008 ).…”
Section: Apoptotic Resistance and The Underlying Mechanism In Sncsmentioning
confidence: 99%
“…The senolytic effects of tamatinib were strongly associated with the inhibition of cell survival pathways through the reduced phosphorylation of both focal adhesion kinase (FAK) and p38-MAPK. Interestingly, navitoclax can further potentiate the senolytic activity of tamatinib, suggesting that, alone or in combination with other drugs, tamatinib represents a good candidate for further investigation [196]. In conclusion, the elimination of senescent cells by the inhibition of the central anti-apoptotic factors and their upstream regulatory pathways represents an effective strategy for targeting cancer cell senescence.…”
Section: Senolytic Therapiesmentioning
confidence: 95%